Solidarity against healthcare access restrictions on undocumented immigrants in Spain: the REDER case study - Maider Urtaran-Laresgoiti; Janire Fonseca Peso; Roberto Nuño-Solinís (BMC, 2019)
Abstract Background In the context of public expenditure reduction and cuts, in 2012, the Spanish government approved the RDL 16/2012, which significantly affected the core values of the national health system. The measure particularly affected undocumented immigrants over 18 years of age, excluding them from accessing the full range of healthcare services in Spain, except for emergency care. In 2014, Red de Denuncia y Resistencia al RDL 16/2012 (REDER) was created as a public awareness and resistance network to defend universal access to healthcare and to stop its infringement. This study aims to analyse the social impact of REDER as a solidarity movement in response to the exclusion of undocumented immigrants from their universal right to health. Methods Qualitative research methodologies were used for the research. Data were collected between November 2017 and December 2017, using eight semi-structured interviews with key informants from the main REDER stakeholders. Additionally, key publications, documents, and presentations of researchers and experts in the field were analysed. For data analysis, a framework extracted from the literature on exclusionary and transformative dimensions of solidarity was used to identify barriers and drivers in REDER's intervention. Results From its creation to the present, REDER has been able to achieve many of its objectives to defend the right to medical care of groups in irregular situations, contributing to the identification of 4,755 cases of discrimination in healthcare access and helping solve over 90% of these cases by delivering either healthcare assistance or administrative support. REDER has also played an important role in: stimulating social activation and empowering citizens to claim their fundamental rights, organising actions against restrictions on accessibility and creating synergies to restore universal healthcare coverage. Conclusions REDER has been shown to be effective in leading the defence of universal healthcare rights, and some achievements in the years following 2012 could be directly attributed to the work done by the network, such as the elimination of legal requirements to obtain health cards or the reduction of the minimum time required to access healthcare. Despite context particularities, the initiatives and main actions of this network may be implemented in other settings that are facing similar limitations to healthcare access, in order to address injustices and promote solidarity.